El muestreo de áreas: una alternativa para estimar características poblacionales ante la ausencia de datos censales. (ING) - Chaves Esquivel, Edwin (1997)
This paper discusses the use of area sampling for providing estimates of population characteristics of a determined area. For this purpose census tracts of the last Population and Housing Census are used. The technique was applied to data gathered in the canton of San Rafael of Heredia. The results show that the technique is a good alternative for the estimation of certain population characteristics when census data ARE not available.